2021
DOI: 10.1002/admt.202001131
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Design‐of‐Experiments Approach for Device Performance Prediction and Optimization of Flash‐Evaporated Organic–Inorganic Halide Perovskite‐Based Photodetectors

Abstract: Single‐source flash evaporation method has recently gained attention for its potential as a rapid and solvent‐free deposition method for producing organic–inorganic halide perovskite (OHP) films in large‐scale. However, due to a complex nature of the different experimental parameters involved in the deposition process, it is not straightforward to obtain the optimal condition for producing high‐quality OHP films. In this study, this problem is tackled by employing the design‐of‐experiment (DoE) process, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…[42] The perovskite film was then deposited through the single-source evaporation method, as we previously reported. [43,44] The detailed fabrication process is described in the Experimental Section and depicted in Figure S1, Supporting Information. Figure 1b shows images sequentially magnified from a whole substrate piece to a molecular junction from left to right in order: entire and enlarged optical microscope images of fabricated molecular junction devices on substrates, an atomic force microscope (AFM) image of a hole with a radius of 2 µm, and a cross-sectional transmission electron microscope (TEM) image of a molecular junction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[42] The perovskite film was then deposited through the single-source evaporation method, as we previously reported. [43,44] The detailed fabrication process is described in the Experimental Section and depicted in Figure S1, Supporting Information. Figure 1b shows images sequentially magnified from a whole substrate piece to a molecular junction from left to right in order: entire and enlarged optical microscope images of fabricated molecular junction devices on substrates, an atomic force microscope (AFM) image of a hole with a radius of 2 µm, and a cross-sectional transmission electron microscope (TEM) image of a molecular junction.…”
Section: Resultsmentioning
confidence: 99%
“…[50] Therefore, we used the single-source evaporation method to deposit a high-quality film of OHP with high uniformity and without pinholes, regardless of the surface energy on the substrate material. [43,44] First, MAPbI 3 powder, which can be used as the flash-evaporation source, was synthesized with high purity and characterized by powder X-ray diffraction (XRD) spectra (Figure S2, Supporting Information). Field-emission scanning electron microscope (FE-SEM) images, shown in Figure 1f, confirmed that a pinhole-free and uniform MAPbI3 film with a film thickness of ≈200 nm was formed by the flash evaporation (bottom image of Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[49][50] Another factor that slows down the progress is the use of one-step-at-atime classical systematic experimentation procedure that has a substantial disadvantage of not considering interactions between input parameters. 51 Remarkably, RPP perovskite precursor solutions at molar concentrations (M) below ~0.7 M crystalize into uniform and highly crystalline films when deposited via a simple drop-casting technique. [52][53] An interesting method was employed in 2021 by Zuo et al, 54 who used a simple drop casting methodology on mildly preheated substrates for perovskite fabrication.…”
Section: Introductionmentioning
confidence: 99%